Neuropathy‐associated histidyl‐tRNA synthetase variants attenuate protein synthesis in vitro and disrupt axon outgrowth in developing zebrafish. (6th July 2020) - Mullen, Patrick; Abbott, Jamie A.; Wellman, Theresa; Aktar, Mahafuza; Fjeld, Christian; Demeler, Borries; Ebert, Alicia M.; Francklyn, Christopher S.
Abstract : Charcot‐Marie‐Tooth disease (CMT) encompasses a set of genetically and clinically heterogeneous neuropathies characterized by length‐dependent dysfunction of the peripheral nervous system. Mutations in over 80 diverse genes are associated with CMT, and aminoacyl‐tRNA synthetases (ARS) constitute a large gene family implicated in the disease. Despite considerable efforts to elucidate the mechanistic link between ARS mutations and the CMT phenotype, the molecular basis of the pathology is unknown. In this work, we investigated the impact of three CMT‐associated substitutions (V155G, Y330C, and R137Q) in the cytoplasmic histidyl‐tRNA synthetase (HARS1) on neurite outgrowth and peripheral nervous system development. The model systems for this work included a nerve growth factor‐stimulated neurite outgrowth model in rat pheochromocytoma cells (PC12), and a zebrafish line with GFP/red fluorescent protein reporters of sensory and motor neuron development. The expression of CMT‐HARS1 mutations led to attenuation of protein synthesis and increased phosphorylation of eIF2α in PC12 cells and was accompanied by impaired neurite and axon outgrowth in both models. Notably, these effects were phenocopied by histidinol, a HARS1 inhibitor, and cycloheximide, a protein synthesis inhibitor. The mutant proteins also formed heterodimers with wild‐type HARS1, raising the possibility that CMT‐HARS1 mutations cause disease through a dominant‐negative mechanism. Overall, these findings support the hypothesis that CMT‐ HARS1 alleles exert their toxic effect in a neuronal context, and lead to dysregulated protein synthesis. These studies demonstrate the value of zebrafish as a model for studying mutant alleles associated with CMT, and for characterizing the processes that lead to peripheral nervous system dysfunction. Abstract : Peripheral neuropathy‐associated histidyl‐tRNA synthetase (HARS) variants form heterodimers with wild‐type HARS and disrupt peripheral nervous system structure and function. Defects in neurite outgrowth are linked to attenuation of protein synthesis and induction of eIF2α phosphorylation. The cellular effects of mutant HARS were phenocopied by inhibition of HARS activity (histidinol) or protein synthesis (cycloheximide). These results suggest that HARS inhibition and dysregulated protein synthesis may be key pathogenic processes in peripheral neuropathy.